THE INFLUENCE OF THE CONTEXTUAL TEACHING AND LEARNING MODEL ON FRACTION LEARNING OUTCOMES AT STATE ELEMENTARY SCHOOL 1 KAMARIAN, SERAM BAGIAN BARAT PROVINSI MALUKU - Pattimukay, Nessy; Takaria, Johanis; Kainama, Benny (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2024)
This research aims to determine the effect of the Contextual Teaching and Learning (CTL) learning model on fraction learning outcomes. The method used is quantitative with a quasi-experimental type of research and is designed using one group pretest-posttest. The research involved fifth-grade students at Kamarian 1 State Elementary School, West Seram Regency. The research results show that there is an influence of the CTL model on fraction learning outcomes. The use of the CTL model can improve fraction learning outcomes, where the average increase in the high category is 71%, medium 48%, and low 29%. The increase is due to the effective use of contextual models, where with contextual learning students can relate the real world to mathematical problems. Contextual learning can facilitate students to see the meaning of the problems they encounter and can relate these problems to the students' real-life context.